(untitled) (Research, Society and Development, 2021)
The present study proposes a didactic sequence with the use of comic books (comics) contextualized about the ABO system and the Rh factor aimed at teaching genetics. Thus, it is a qualitative descriptive research, in which the steps of a didactic sequence created from three pedagogical moments are detailed: initial problematization, knowledge organization and knowledge application. The first moment consists of the presentation of the content, from contextualized comics and guiding questions, so it is possible to assess the students’ prior knowledge about the content that will be worked on. The second moment consists of explaining the content based on the information presented in the comics. At this stage, students will be able to acquire the necessary knowledge to understand the content present in the comics. The third and last moment is a proposal for the construction of comic books by the students, so that the knowledge obtained in the classroom can be disseminated later. From this didactic sequence, the content can be worked on in a playful way, using comic books as a didactic resource, and considering everyday situations and the students’ prior knowledge.